2014
DOI: 10.1097/ccm.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Circulating miR-133a Are Elevated in Sepsis and Predict Mortality in Critically Ill Patients

Abstract: miR-133a serum levels were significantly elevated in critical illness and sepsis. High miR-133a levels were associated with the severity of disease and predicted an unfavorable outcome of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 27 publications
2
115
0
1
Order By: Relevance
“…In patients in shock related to sepsis and organ failure, significant correlations between miR-133a and disease severity have been revealed; patients with an APACHE-II score above 10 had significantly higher miR-133a levels than those with an APACHE-II below 10 [54]. The study by Tacke et al illustrates that specific miRNAs can be used as predictors for an unfavorable prognosis, and for both short-and long-term mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 92%
“…In patients in shock related to sepsis and organ failure, significant correlations between miR-133a and disease severity have been revealed; patients with an APACHE-II score above 10 had significantly higher miR-133a levels than those with an APACHE-II below 10 [54]. The study by Tacke et al illustrates that specific miRNAs can be used as predictors for an unfavorable prognosis, and for both short-and long-term mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 92%
“…Roderburg et al, investigated the microRNAs expression in patients with sepsis, reporting an increase in microRNA-150 expression (Roderburg et al 2013). Tacke et al, underwent a similar study which proved a rise in microRNA-133a expression (Tacke et al 2014). Sun et al, documented the modifications seen in microRNAs expression in patients suffering from sepsis, along with which he noted a significant fall in microRNA-181b concentration (Sun et al 2012).…”
Section: The Micrornas Expression In Sepsis and Its Implications In Nmentioning
confidence: 94%
“…MicroRNAs (miRNAs) are a class of gene products that are implicated in several lung diseases [23][24][25] and have emerged as novel biomarkers 26 and possible therapeutic strategies. 27 Recent studies revealed that miR-21 was dynamically regulated in LPS-induced ALI.…”
mentioning
confidence: 99%